2021
DOI: 10.3390/math9172068
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approach for Modeling and Control of a Commercial Heliocentris FC50 PEM Fuel Cell System

Abstract: In recent years, machine learning (ML) has received growing attention and it has been used in a wide range of applications. However, the ML application in renewable energies systems such as fuel cells is still limited. In this paper, a prognostic framework based on artificial neural network (ANN) is designed to predict the performance of proton exchange membrane (PEM) fuel cell system, aiming to investigate the effect of temperature and humidity on the stack characteristics and on tracking control improvements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In this research, we aimed to design controllers which could follow a reference current named Iref ${I}_{\mathrm{ref}}$ and established in Derbeli et al 41 The involved structures are an FLC‐T1 and FLC‐T2 which will be explained in the following section. Major contrasts are in terms of robustness, control signal, and capacity for tracking.…”
Section: Methodsmentioning
confidence: 99%
“…In this research, we aimed to design controllers which could follow a reference current named Iref ${I}_{\mathrm{ref}}$ and established in Derbeli et al 41 The involved structures are an FLC‐T1 and FLC‐T2 which will be explained in the following section. Major contrasts are in terms of robustness, control signal, and capacity for tracking.…”
Section: Methodsmentioning
confidence: 99%
“…The statistics of papers submitted to this Special Issue for both published and rejected items are as follows: 23 total submissions, of which 16 were published (69.6%) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and 7 rejected (30.4%). The authors' geographical distribution is shown in Table 1, where it can be seen that the 67 authors are from 13 different countries.…”
Section: Statistics Of the Special Issuementioning
confidence: 99%
“…et.al. [19] had shown how to model a system with the help of predictive control along with machine learning. These types of modeling are able to track the system with higher efficiency.…”
Section: Dynamics Of Mechanical System-a Literature Reviewmentioning
confidence: 99%